2005
DOI: 10.1038/nature04152
|View full text |Cite
|
Sign up to set email alerts
|

An induced-fit mechanism to promote peptide bond formation and exclude hydrolysis of peptidyl-tRNA

Abstract: The large ribosomal subunit catalyses the reaction between the alpha-amino group of the aminoacyl-tRNA bound to the A site and the ester carbon of the peptidyl-tRNA bound to the P site, while preventing the nucleophilic attack of water on the ester, which would lead to unprogrammed deacylation of the peptidyl-tRNA. Here we describe three new structures of the large ribosomal subunit of Haloarcula marismortui (Hma) complexed with peptidyl transferase substrate analogues that reveal an induced-fit mechanism in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
208
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(217 citation statements)
references
References 27 publications
7
208
2
Order By: Relevance
“…Like A2602, also U2585 has been shown to be a structurally flexible residue in the catalytic cavity of the PTC in various 50S subunit crystal structures (6,7,9,11,26,45). Furthermore, mutations at this base also showed reductions in peptide release activities, albeit to a weaker extent compared to A2602 (24,25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like A2602, also U2585 has been shown to be a structurally flexible residue in the catalytic cavity of the PTC in various 50S subunit crystal structures (6,7,9,11,26,45). Furthermore, mutations at this base also showed reductions in peptide release activities, albeit to a weaker extent compared to A2602 (24,25).…”
Section: Resultsmentioning
confidence: 99%
“…In fact all of them showed slightly enhanced (∌ 2-fold) peptide release rates (Table 1). Based on crystallographic studies it has been suggested that the base of U2585 protects the ester bond of P-site-bound peptidyl-tRNA from premature hydrolysis during the elongation phase of protein synthesis (9). We therefore tested if the accelerated peptide release rates of the abasic 2585 subunit are the result of an RF-independent peptidyl-tRNA hydrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of translation termination, nascent proteins will be inserted into the membrane but will also still be attached to the ribosome via the P site bound peptidyl-tRNA. It is understood that this ester bond can be spontaneously hydrolyzed over time, but release factor activity at the ribosome dramatically accelerates this natural process (Schmeing et al., 2005). However, it is possible that subtle temporal effects on the assembly process following siRNA-mediated knockdown may lead to assembled complexes with minor defects in electron transfer, leading to increased loss of electrons in the form of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…The conformations of 23S rRNA nucleotides U2584 and U2585 were taken from the equivalent nucleotides of the Haloarcula marismortui 50S subunit in complex with the unaccommodated A-site tRNA mimic (PDB1VQ6) 21,22 after the PDB was fitted as a rigid body into the ErmBL-SRC density map. The conformation of U2506 was similar to the equivalent nucleotide of the Haloarcula marismortui 50S subunit in complex with the accommodated A-site tRNA mimic (PDB1VQN) 21,22 , however required manual rotation of the base to prevent clashing with the unaccommodated position of U2585. In contrast, the conformation of A2062 present in the ErmBL-SRC is unique, being distinct from the tunnel “in” (PDB3CC2) 38 and tunnel “out” (PDB1VQ6) 21,22 conformations observed in previously reported ribosome structures.…”
Section: Methodsmentioning
confidence: 99%